PENINGKATAN PRODUKSI PERTANIAN MENGGUNAKAN DC PV PUMP UNTUK DESA BINAAN MULYOARJO LAWANG - Aripriharta, Aripriharta; Susilo, Suhiro Wongso; Faidzin, Ilham; Sujito, Sujito; Hadi, Mokh. Sholihul; Zubaidah, Siti; Yazid, Muhammad (LPPM Univ. Ibn Khaldun Bogor, 2024)
According to PLN data, electricity demand in Indonesia continues to grow until November 2022, reaching 3,128.8 MVA with 193,058 customers in the Agricultural Electrification (EA) sector. Indonesia has solar energy potential reaching 2,898 GW, but only 0.2 GW has been installed until 2021. In Mulyoarjo Village, Lawang District, our partners hope to utilise solar energy to support agriculture. The partner location has good sunlight potential for solar panel installation. This community service activity aims to apply Photovoltaic-Based Renewable Power technology (TTG DC PV Pump) to increase agricultural productivity in partner villages. The implementation method involves survey, design, installation, field test, and handover. The results showed that the peak of solar illumination occurred at 11.30 am with a voltage of 13.5V and a current of 14.58A on the solar panel. These findings can be the basis for improving agricultural efficiency in Mulyoarjo Village by optimally utilising the available solar energy.